“ART AND CULTURE” LEARNING MANAGEMENT FOR STUDENTS’ INCREASED ACHIEVEMENT DURING THE COVID-19 PANDEMIC - Anna Shopia Adham; Fitri Nur Mahmudah (JURNAL AL-TANZIM, 2021)
One of the keys to the success of learning is good management. During the Covid-19 pandemic, teachers need managerial skills for the learning process to take place. The purpose of this study is to determine the management of learning arts and culture to improve student achievement during the Covid-19 pandemic. The study employed the qualitative approach to research. Data collection techniques used were interviews, observation, and documentation. The results of this study indicate that the learning management that teachers need to do in Art and Culture is due to the characteristics, creation, communication, motivation, learning strategies, and discipline. The recommendations of this research can be used by teachers in developing culture and art learning during the Covid-19 pandemic. Hence, teachers will be able to provide learning to students, and students can attain improved skills and good learning outcomes.